(untitled) (African Disability Rights Yearbook, 2021)
Girls with disabilities are subjected to multiple challenges due to their disabilities. They face discrimination that most women face. They are discriminated due to their disabilities. They encounter barriers that most children encounter. This is the double marginalisation that breeds and sustains the dehumanising problems experienced by girls with disabilities. This creates a vulnerable group within a vulnerable group. Most of the times, girls with disabilities are more likely than boys to encounter severe difficulties in accessing education. Fortunately, Malawi passed the Disability Act in 2012 which epitomises the social model approach to disability. The Act attempts - to a large extent - to domesticate the state’s obligations under the Convention on the Rights of Persons with Disabilities (CPRD). The hallmark of the Act is a myriad of rights including the right to education. This is an important right that can facilitate the elimination of most forms of discrimination that girls with disabilities face. However, the realisation of the right to education as provided in the Disability Act is hampered by several socio-legal and physical structural challenges. The Act, by failing to recognise that other persons with disabilities like girls with disabilities are multi-disadvantaged, fails to provide the reasonable accommodation that it purports to advance. The notion of dignity and equalisation of opportunities for persons with disabilities can only be realised if the right to education for girls with disabilities is properly articulated in the Act. Further, the remedial mechanisms provided under the Act and it is contended that the remedies it provides should be simplified to make them ‘user friendly’ to people that are multi-vulnerable - such as girls with disabilities. The paper proposes a more expansive formulation of locus standi in enforcement of the rights provided under the Act. It further appraises administrative penalties provided in the Disability Act.